Abbau von Herbiziden und Fungiziden durch Mikroorganismen des Bodens - Franz Lingens (CHIMIA)
Herbicides and fungicides are chemicals which increase and ameliorate production in agriculture and save manpower. Herbicides are used to control weeds without destruction of useful plants. Fungicides protect plants against the attack of phytopathogenic fungi. Herbicides and fungicides may be dangerous for men and animals if they are not degraded at all or if they are only degraded at a very slow rate. The mechanismus of degradation of some herbicides and fungicides by microorganisms are described. On the occurence of these microorganisms in the various taxonomical groups is reported. Their potential to degrade of natural and foreign substrates is discussed. The knowledge obtained may be useful for the development of new herbicides and fungicides which are degraded easily and thus cause less pollution of the environment.